Fabrication of GaAs/Al0.3Ga0.7As Multiple Quantum Well Nanostructures on (100) Si Substrate Using a 1-nm InAs Relief Layer - Oh, H. J.; Park, S. J.; Lim, J. Y.; Cho, N. K.; Song, J. D.; Lee, W.; Lee, Y. J.; Myoung, J. M.; Choi, W. J. (AMER SCIENTIFIC PUBLISHERS, 2014)
Nanometer scale thin InAs layer has been incorporated between Si (100) substrate and GaAs/Al0.3Ga0.7As multiple quantum well (MQW) nanostructure in order to reduce the defects generation during the growth of GaAs buffer layer on Si substrate. Observations based on atomic force microscopy (AFM) and transmission electron microscopy (TEM) suggest that initiation and propagation of defect at the Si/GaAs interface could be suppressed by incorporating thin (1 nm in thickness) InAs layer. Consequently, the microstructure and resulting optical properties improved as compared to the MOW structure formed directly on Si substrate without the InAs layer. It was also observed that there exists some limit to the desirable thickness of the InAs layer since the MOW structure having thicker InAs layer (4 nm-thick) showed deteriorated properties.
Keywords: MOLECULAR-BEAM EPITAXY; GROWTH; SILICON; GAAS; SUPERLATTICES; SEMICONDUCTORS; ISLANDS